Comparison of the University Pharmacy Education Programs in Germany and Vietnam - Daniel Baecker; Do Thi Mai Dung; Hai Pham-The; Nguyen Hai-Nam (MDPI AG, 2022)
During the global COVID pandemic, the importance of professionals in the health care sector has been put in a new light, including pharmacists. In this context, the focus is also on how pharmacists are trained in different countries. Through an exchange of pharmacy teaching staff from a German to a Vietnamese university, the pharmacy education programs in both countries were compared. Aspects such as access to studies, structure of studies, and further training opportunities were considered. Differences and similarities emerged. In both countries, students first acquire basic knowledge and then delve deeper into pharmaceutical content in main studies. There is, expectedly, a great overlap in the content of the courses. Overall, the education at Vietnamese universities seems to be more practice-oriented due to a large number of placements. This also allows a specialization, which can be pursued in Germany with self-interest after graduation. There, the preparation for everyday work in the community pharmacy is separated from the university by a mandatory practical year. For the future, efforts are being made in both countries to strengthen the importance of clinical pharmacy in the curriculum. To this end, the Vietnamese are taking their inspiration from abroad in many cases, including Germany.